The authority of knowledge systems between the ethics of writing and the discourse system in structural thought - Aziz, Mohamed Hato (Al-Adab Journal, 2022)
The word ethics came from ethics, which is the practical expression of religions, meaning the deliberative practice of the rules of religion (behavior and practical application of the principles of religions). But after the intellectual and philosophical revolutions in the post-modern period, this concept began to move away from its initial meaning to correspond to the meaning of restriction, or the coercive conditions that guarantee belonging to a sect, party, or intellectual movement, or oblivion from a specific ideology. In other words, every sect, idea, or party has its own morals.